Assessment of Arbuscular Mycorrhizal Association in Some Fruit Plants in Bangladesh - Khanam, Delowara (Bangladesh Journal of Microbiology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Â Rhizosphere soils of 19 fruit plants from horticultural farm of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur were assessed for arbuscular mycorrhiza (AM) spore population and determining colonization in their roots. The spore numbers recorded ranged from 48.0 (Citrus limon) to 1,050 (Annona reticulata) per 100 g soil in 2004, 41.0 (Citrus grandis) to 916.7 (Phyllanthus emblica) in 2005 and 44.3 (Citrus grandis) to 575.0 (Syzygium samarangense, white) in 2006. A considerable variation was observed in average spore numbers recorded in three consecutive years. Different fruit plants showed different percentages of root colonization by AM fungi. Among all the fruit plants, the highest colonization (86.7%) was found in Syzygium jambos and Elaeocarpus floribundus and the lowest colonization (20.0%) was recorded in Syzygium samarangense (red). Keywords: Arbuscular mycorrhiza (AM), Colonization, Spore population, Fruit plants DOI: http://dx.doi.org/10.3329/bjm.v24i1.1234 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 34-37